A COMPARISON OF INTRAVENOUS PARACETAMOL AND FENTANYL FOR PAIN RELIEF DURING AND AFTER DILATATION AND EVACUATION - Chopade, Nitin P (Journal of Biomedical and Pharmaceutical Research, 2020)
BACKGROUND: It is necessary to employ pain management techniques because dilatation and evacuation operations can be uncomfortable. In obstetrics, dilatation and evacuation are routine daycare procedures. Nevertheless, the woman had a bad experience—both during and after the treatment. Paracetamol is a reliable and effective analgesic for mild to severe pain. Improved predictability and tolerability are potential benefits of the IV form of this medicine when compared to oral or rectal delivery modalities. After 15 to 20 minutes, it easily penetrates the blood-brain barrier and starts to work as a central analgesic. Four hours in, these effects begin to diminish. It is preferred in most surgical patients since it has no effect on mental state, bleeding, respiratory drive, stomach mucosa integrity, or renal function. Therefore, the purpose of this study was to compare the effects of intravenous fentanyl and paracetamol on pain management during and after dilatation and evacuation surgery. AIM: The aim of the study was to compare paracetamol with fentanyl for pain relief in dilatation and curettage procedures. MATERIAL AND METHOD: A prospective, randomized, interventional study was conducted in the anesthesia department. Every patient received a thorough pre-anesthesia examination, and all required laboratory testing was completed. After the patients were informed about the study in a way that they could comprehend, they gave their informed consent. The study included 50 patients, 25 in each group, who were scheduled for elective and emergency dilatation and evacuation under general anesthesia and were members of the American Society of Anesthesiologists I and II fit. RESULTS: We examined fifty patients who required general anesthesia and elective D&E because they had missed their planned abortions. Random selection was used to assign patients to receive IV fentanyl and paracetamol. The measured vital signs did not show any significant differences in mean heart rate, blood pressure (systolic, diastolic, and mean arterial pressure), or respiration between the two groups during the study. There were no withdrawals from the trial. It was discovered that there was no statistically significant difference between the groups with regard to age, weight, height, and ASA status. In the recovery room, the visual analog scale (VAS) was used to score the patient’s pain at 5, 15, and 30 minutes. Both groups experienced mild discomfort at five minutes; the mean pain scores for the fentanyl and paracetamol groups were 0.85 ± 1.2 and 1.45 ± 1.1, respectively. CONCLUSION: The study provides evidence for the usefulness of IV paracetamol by demonstrating how it functions similarly to fentanyl in reducing pain during dilatation and curettage procedures. Our study backs up the usage of a single Inj injection. For both intraoperative and postoperative pain relief management in dilatation and evacuation, paracetamol was injected intravenously at a dose of 15 mg/kg body weight. This was done because the hemodynamic profile was stable, there was no respiratory depression, no significant drug-related complications, and the VAS score was favorable. KEYWORDS: Fentanyl, Pain, Paracetamol, Dilatation and Evacuation, Non-Opioid Analgesics, Recovery of Function and Patient Satisfaction